USG in evaluation of patients with scrotal pain - Chhetri, PK; Tayal, A; Deka, PK (Journal of College of Medical Sciences-Nepal, 2012)
Based on physical examination alone it is often difficult to accurately make a clinical diagnosis and decide whether a palpable scrotal pathology arises from the testis itself or from extratesticular elements within the scrotum. Clinical examination of the testis is especially difficult due to pain, tenderness or when obscured by a large hydrocele. The aim of the study was thus undertaken to evaluate the role of ultrasonography (USG) in patients presenting with scrotal pain. 50 patients who presented to the surgical department with scrotal pain were subjected to USG. The commonest cause for scrotal pain was epididymitis with or without orchitis (40 %), followed in descending order by cystic lesions of the epididymis (18 %), varicocele (12 %), trauma (8 %), torsion (4 %) and tumour (2 %). No abnormality was seen on USG in 7 patients ( 14 %). This study concludes that USG is a sensitive and specific examination in patients with scrotal pain. Besides differentiating testicular from extratesticular origin it can also differentiate solid from cystic masses. Colour flow imaging is especially helpful in varicocele and testicular torsion. Torsion of the testis remains the most urgent and important entity dependent on USG for diagnosis. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 18-22 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6821